WORKPLACE SEXUAL HARASSMENT: A STUDY OF FEMALE NURSES FROM HEALTHCARE INSTITUTES OF LAHORE, PAKISTAN. - Shahzadi, Reena; Arshad, Muhammad; Afzal, Dr Afzaal (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2023)
Workplace sexual harassment of women is an imperative aspect and one of the most challenging impediments in the process of gender equality and women empowerment globally. Today’s women proved themselves through more productive roles and claimed equal collective rights along with better access to resources, acceptance, security, and self-respect in their families, communities, and workplaces. The increasing involvement of women in the workforce increases the incidents of sexual harassment at the workplace and become the largest hindrance towards women psycho-social and economic empowerment. To understand the actual situation this descriptive study was carried out with the female nursing staff in various public hospitals of Lahore. A structured self-administered questionnaire was utilized to collect primary data through multistage simple random sampling methods. Various univariate, bivariate and multivariate statistical analyses were applied through SPSS-21 for comprehensive understanding and coherent discussion. The findings reveled that a huge proportion of the study population faces sexual harassment in the workplace. Male staff especially doctors and male nurses were found to be the most common perpetrators of sexual harassment against female nurses. The participants reported that sexual harassment in the workplace is a serious problem that significantly impacts the social, psychological, physical, and economic condition and productivity of female nurses.